Social Influences on Decisions to Refrain or Desist from Two Common Crimes among Incarcerated Men. Issue 1 (1st January 2022) - Bouffard, Jeff A.; Niebuhr, Nicole
ABSTRACT: Desistance scholars have increasingly focused on what is conceived of as a lengthy process of moving away from criminality, especially the central role of the individual making a decision to do so. Control theories may be especially useful in understanding this process, given their emphasis on social influences that may restrain individuals from crime. Research on control theories has often examined marriage, employment, family bonds, and belief in the law, as well as the impact of one's internal level of self-control. Using survey data and hypothetical vignettes depicting drunk driving and aggravated assault, we examine a number of widely used social control variables, and other influences on decisions to refrain, and desist from these two common offenses. Among 428 incarcerated males, having a romantic partner significantly increased the likelihood of conformity, while having antisocial peers and having engaged in prior similar offenses significantly decreased the likelihood of conformity. Importantly, each of these effects appeared to vary by offense type. Implications for future research on the desistance process and control theories are discussed, as are implications for effective correctional services that seek to promote desistance and successful community reintegration.